Comparison of coconut water and a carbohydrate-electrolyte sport drink on measures of hydration and physical performance in exercise-trained men - Kalman Douglas S; Feldman Samantha; Krieger Diane R; Bloomer Richard J (Taylor & Francis Group, 2012)
Abstract Background Sport drinks are ubiquitous within the recreational and competitive fitness and sporting world. Most are manufactured and artificially flavored carbohydrate-electrolyte beverages. Recently, attention has been given to coconut water, a natural alternative to manufactured sport drinks, with initial evidence indicating efficacy with regard to maintaining hydration. We compared coconut water and a carbohydrate-electrolyte sport drink on measures of hydration and physical performance in exercise-trained men. Methods Following a 60-minute bout of dehydrating treadmill exercise, 12 exercise-trained men (26.6 ± 5.7 yrs) received bottled water (BW), pure coconut water (VitaCoco®: CW), coconut water from concentrate (CWC), or a carbohydrate-electrolyte sport drink (SD) [a fluid amount based on body mass loss during the dehydrating exercise] on four occasions (separated by at least 5 days) in a random order, single blind (subject and not investigators), cross-over design. Hydration status (body mass, fluid retention, plasma osmolality, urine specific gravity) and performance (treadmill time to exhaustion; assessed after rehydration) were determined during the recovery period. Subjective measures of thirst, bloatedness, refreshed, stomach upset, and tiredness were also determined using a 5-point visual analog scale. Results Subjects lost approximately 1.7 kg (~2% of body mass) during the dehydrating exercise and regained this amount in a relatively similar manner following consumption of all conditions. No differences were noted between coconut water (CW or CWC) and SD for any measures of fluid retention (p > 0.05). Regarding exercise performance, no significant difference (p > 0.05) was noted between BW (11.9 ± 5.9 min), CW (12.3 ± 5.8 min), CWC (11.9 ± 6.0 min), and SD (12.8 ± 4.9 min). In general, subjects reported feeling more bloated and experienced greater stomach upset with the CW and CWC conditions. Conclusion All tested beverages are capable of promoting rehydration and supporting subsequent exercise. Little difference is noted between the four tested conditions with regard to markers of hydration or exercise performance in a sample of young, healthy men. Additional study inclusive of a more demanding dehydration protocol, as well as a time trial test as the measure of exercise performance, may more specifically determine the efficacy of these beverages on enhancing hydration and performance following dehydrating exercise.